2000
DOI: 10.1161/01.hyp.35.4.1009
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hypertension in a Rat Model of Diet-Induced Obesity

Abstract: Abstract-Although obesity is a risk factor for hypertension, the relationship between these 2 conditions is not well understood. Therefore, we examined some parameters of hypertension and cardiovascular disease in a dietary model of obesity. Male Sprague-Dawley rats were provided either a control diet (C) or a diet containing 32% kcal as fat (similar to a Western diet) for 1, 3, or 10 weeks. Rats in the latter group diverged based on body weight gain into obesity-prone (OP) and obesity-resistant (OR) groups. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
213
5
18

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(272 citation statements)
references
References 50 publications
36
213
5
18
Order By: Relevance
“…Adjustment of litter size or, more to the point, adjustment of early feeding patterns can influence adult blood pressure (42,45), as can the type of diet (13). In the current study, we also observed an increase in blood pressure as animals fed the high-fat diet gained weight.…”
Section: Discussionsupporting
confidence: 66%
“…Adjustment of litter size or, more to the point, adjustment of early feeding patterns can influence adult blood pressure (42,45), as can the type of diet (13). In the current study, we also observed an increase in blood pressure as animals fed the high-fat diet gained weight.…”
Section: Discussionsupporting
confidence: 66%
“…25 Therefore, in this study, we decided to test whether blood pressure, measured in freely moving obesity-prone rats, can be increased by a diet with higher fat content (60% of total calorie), fed for a longer period (24 weeks) compared with the 32% HF diet fed for 10-12 weeks in earlier rat studies. [21][22][23] This diet treatment led to significantly elevated body weight and dyslipidemia; however, the plasma insulin and glucose levels were not elevated compared with chow-fed rats. This could be because both our control and HF diet-fed rats were selectively bred obesity-prone rats that show signs of metabolic syndrome even when fed with regular chow.…”
Section: Discussionmentioning
confidence: 92%
“…20 However, HF feeding in rats led to mixed results. Although some studies reported significant increases in blood pressure using tail cuff measurements, 21,22 others that used telemetry showed no change. 23 In addition, the question was raised that higher blood pressure values measured with tail cuff in HFfed animals were the result of an augmented stress response to restraint accompanying this blood pressure measurement procedure.…”
Section: Discussionmentioning
confidence: 99%
“…They include the activation of the renin -angiotensin system, 8,9 high levels of circulating leptin, 10 reduced growth hormone concentration, 11 and activation of the sympathetic nervous system. 12 Although animal studies in rats have shown that obesity is associated with increased myocardial oxidative stress 13 and increased lipid peroxidation, 14 to the best of our knowledge there is no report in the literature of the effect of obesity per se on lipid peroxidation and erythrocyte cytoprotection in humans.…”
Section: Introductionmentioning
confidence: 99%